Relationship of Emotional Intelligence and Self-regulation of Male Elite Swimmers - Ahad Sadri; Hamid Janani (The Society of Aging and Physical Activity (SAPA), 2015)
Emotional intelligence (EI) is itself an important factor in predicting individual performance and has been introduced as the strongest force for leadership and success. The aim of this study was to evaluate the correlation between EI and self-regulation (SR) in elite male swimmers of East Azerbaijan Province, Iran. The subjects included 100 male athletes participating in East Azerbaijan Province swimming championships held in Tabriz from 18-21 March, 2014. Mean age and mean years of training records in swimming subjects were equal to 22.86±6.86 and 11±6.51, respectively. To collect the required data, Emotional Intelligence Questionnaire of Bradberry and Greaves and Self-regulation Questionnaire of Brown, Miller and Lawendowski were used. The results showed that there is a significant positive correlation between total scores of EI and SR. Also, all components of EI (except social awareness) had a positive significant correlation with the total SR score. Among the components of EI, social awareness had a negative significant relationship with SR. The findings suggest that EI and SR consist of the same infrastructure and this fact can justify the high correlation between them.